Study on Cleaning Effect of Different Water Flows on the Pulsed Cavitating Jet Nozzle - Chengting Liu; Gang Liu; Zuoxiu Yan (Shock and Vibration)
The method of cleaning by self-excited pulsed cavitating jet was proposed according to cleaning characteristics and requirements of large storage equipment. This method has many advantages compared with other cleaning methods. In order to achieve the optimum cleaning effects, experimental research on working status of the nozzle at different flow rates was conducted and analysis was carried out from the following four aspects: cavitation morphology, pressure pulse frequency, velocity fluctuation amplitude, and erosion effect. The research results showed that flushing effects in the nozzle without cavitation were far below those with cavitation; when the flow rate increased to over 2.7 m3/h, cavitation began to appear in the chamber. When Q = 7.2 m3/h, the velocity fluctuation amplitude was about 17.25 m and pressure fluctuation occurred for 86 times (maximum) within 1 s. During the experiment on erosion effects, the flow rate had little influence on outside diameter of the erosion circle. The erosion rate increased with the increase of the flow rate, reached the peak value at Q = 7.2 m3/h, but slightly decreased subsequently.